1972
DOI: 10.1051/rphysap:019720070101100
|View full text |Cite
|
Sign up to set email alerts
|

Electric dipole radiation at vlf in a uniform warm magneto-plasma

Abstract: Reçu le 20 septembre 1971) Résumé. 2014 Cet article traite des caractéristiques de rayonnement à très basse fréquence d'une antenne dipolaire mince dans un magnétoplasma tiède. Les solutions formelles sont obtenues pour la partie de la résistance de rayonnement due aux modes thermiques (Rt) et au mode sifflement (Rw). Dans ce calcul, les ions sont supposés au repos, et les effets de température non nulle sont introduits au moyen d'un terme de pression scalaire. Deux orientations particulières du dipôle sont pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…Thus, increasing the cell resolution beyond 30 cells does not adversely affect the impedance values since the waves dominating the energy flow are well resolved. This observation is supported by [12] and [13] where it was found that dipole antennas operating in a magnetized plasma environment preferentially radiate waves whose wavelength is on the order of the antenna length.…”
Section: Computational Mesh Considerationsmentioning
confidence: 68%
See 4 more Smart Citations
“…Thus, increasing the cell resolution beyond 30 cells does not adversely affect the impedance values since the waves dominating the energy flow are well resolved. This observation is supported by [12] and [13] where it was found that dipole antennas operating in a magnetized plasma environment preferentially radiate waves whose wavelength is on the order of the antenna length.…”
Section: Computational Mesh Considerationsmentioning
confidence: 68%
“…FDFD simulations are carried out for dipole antennas oriented perpendicular with respect to the ambient static magnetic field. This orientation is chosen since the antenna pattern and power delivery are optimal for launching waves parallel to the static magnetic field [12], [13]. Antennas considered for the purpose of our application are on the order of 100 m in length and up to 20 cm in diameter.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations